2017
DOI: 10.1136/bmjopen-2016-014365
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles and UltraSound-accelerated Thrombolysis (MUST) for peripheral arterial occlusions: protocol for a phase II single-arm trial

Abstract: IntroductionAcute peripheral arterial occlusions can be treated with intra-arterial catheter-directed thrombolysis as an alternative to surgical thromboembolectomy. Although less invasive, this treatment is time-consuming and carries a significant risk of haemorrhagic complications. Contrast-enhanced ultrasound using microbubbles could accelerate dissolution of thrombi by thrombolytic medications due to mechanical effects caused by oscillation; this could allow for lower dosages of thrombolytics and faster thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…12 An ongoing phase II clinical trial is investigating the safety and clinical feasibility of USstimulated MBs for thrombolysis. 13 Additionally, another application arises from the increased frequency of femoral artery puncture to access the vasculature in interventional cardiology and interventional radiology. Perforation to the vessel combined with the influence of arterial pressure can form a perfused blood sac that communicates with the vessel lumen.…”
Section: Clinical Utility Of Therapeutic Microbubblesmentioning
confidence: 99%
“…12 An ongoing phase II clinical trial is investigating the safety and clinical feasibility of USstimulated MBs for thrombolysis. 13 Additionally, another application arises from the increased frequency of femoral artery puncture to access the vasculature in interventional cardiology and interventional radiology. Perforation to the vessel combined with the influence of arterial pressure can form a perfused blood sac that communicates with the vessel lumen.…”
Section: Clinical Utility Of Therapeutic Microbubblesmentioning
confidence: 99%
“…41 This method proved to be successful in animal models and in a phase II single-arm clinical trial involving patients with acute peripheral arterial occlusions eligible for thrombolytic treatment. 42 Furthermore, preclinical trials have demonstrated that CEUS was suitable to restore epicardial and microvascular flow after ST-segment elevation myocardial infarction (STEMI) in pigs 43 and a phase II clinical trial is ongoing, evaluating the effect of sonothrombolysis after STEMI (NCT03092089). Unfortunately, several clinical trials addressing sonothrombolysis after STEMI 44 or stroke 13 (EudraCT No 201200032341; NCT#01098981) had to be terminated due to vasoconstriction or increased risk of hemorrhage after multiple US applications, respectively.…”
Section: Therapeutic Ceus In Cardiovascular Applicationsmentioning
confidence: 99%
“…Ebben et al elaborated protocol for a phase II single-arm trial for peripheral arterial occlusions. They highlighted safety of the procedure and reduction of major hemorrhagic complications by lowering thrombolytic drug dosage [45]. Whereas Zhu et al did a clinical study on intra-clot microbubble-enhanced ultrasound thrombolysis for deep vein thrombosis.…”
Section: Gliomamentioning
confidence: 99%